Improper Coordination of BamA and BamD Results in Bam Complex Jamming by a Lipoprotein Substrate - Tata, Muralidhar (mBio, 2019)
The β-barrel assembly machinery, the Bam complex, is central to the biogenesis of integral outer membrane proteins (OMPs) as well as OMP-dependent surface-exposed lipoproteins, such as regulator of capsule synthesis protein F (RcsF). Previous genetic analysis established the model that nonessential components BamE and BamB have overlapping, redundant functions to enhance the kinetics of the highly conserved BamA/BamD core. Here we report that BamE plays a specialized nonredundant role in the Bam complex required for surface exposure of RcsF. We show that the lack of bamE, but not bamB, completely abolishes assembly of RcsF/OMP complexes and establish that the inability to assemble RcsF/OMP complexes is a molecular reason underlying all synthetic lethal interactions of ΔbamE. Our genetic analysis and biochemical cross-linking suggest that RcsF accumulates on BamA when BamA cannot engage with BamD because of its limited availability or the incompatible conformation. The role of BamE is to promote proper coordination of RcsF-bound BamA with BamD to complete OMP assembly around RcsF. We show that in the absence of BamE, RcsF is stalled on BamA, thus blocking its function, and we identify the lipoprotein RcsF as a bona fide jamming substrate of the Bam complex.